Exploring doctors’ and midwives’ perspectives on utilising social media for maternal health promotion - Omoloso , Aisha Imam; Oche , Maria Faustina; Adisa , Rasaq Mohammed; Mahamood , Ahmad Fahmi; Bajuri , Maskor; La’aro , Oba Abdulkadir; Udende , Patrick (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the perspectives and experiences of doctors and midwives in Ilorin, Nigeria, regarding the use of social media for maternal health promotion. Through in-depth interviews with ten healthcare professionals; eight doctors and two midwives, three key themes emerged from thematic analysis: perceptions of social media’s role, practical experiences of its application, and strategies for optimisation. Participants viewed social media, including platforms like WhatsApp, Facebook, and Instagram, as a powerful tool for enhancing patient education, fostering supportive communities, and extending the reach of maternal health information. It facilitates awareness of issues such as postpartum depression, promotes healthier behaviours, and ensures continuous support. However, challenges such as misinformation, privacy concerns, and unrealistic expectations temper its benefits, necessitating credible content and careful management, as supported by Social Cognitive Theory’s emphasis on outcome expectations and self-efficacy. Practically, participants employed varied platforms and interaction methods, direct messages, group chats, and calls, sharing content like videos and infographics, though time constraints, limited training, and poor internet access posed barriers. Proposed optimisation strategies included debunking myths with expert input, government regulation of misinformation, and amplifying credible content through proactive education. This study concludes that while social media holds transformative potential for maternal health, addressing these challenges through training and infrastructure improvements is crucial. By leveraging its strengths, healthcare providers can significantly enhance maternal health outcomes in Nigeria.